Pengaruh Penerapan Metode Kartu Berpasangan dalam Pembelajaran IPS untuk Meningkatkan Hasil Belajar Siswa di MTs Raudhatul Akmal - Fachri Hanafi Saragih; Nurul Anisa Nasution; Syarifah Widya Ulfa (Departement of Mathematics Education, 2023)
This research is motivated by the low interest in student learning in Social Sciences (IPS) subjects. This is due in large part to the fact that most social studies lessons are placed at the end of class, where at the end of the class students begin to feel lazy to study and also sleepy, besides that students are not able to answer the feedback given by the teacher about the material just being taught, students are less involved active in the learning process. Teachers who tend to use the lecture method because social studies studies talk a lot about theory, this makes students more easily bored following lessons and seems difficult to answer test questions. The formulation of the problem in this study is whether the application of cooperative learning through paired card media can improve social studies learning outcomes for students at MTs Raudhatul Akmal Batang Kuis, Medan.